2016
DOI: 10.11648/j.ss.20160504.12
|View full text |Cite
|
Sign up to set email alerts
|

Socio-economic Condition of Plain Land Tribal People in Bangladesh

Abstract: The purpose of the paper is to depict socioeconomic condition of tribal people. The research is based on some primary data, which are collected from a structured questionnaire survey, interview, observation and focus group discussion and also on some secondary data which are collected from different sources. It is found that among tribal people, 60.94% households are involved in agricultural day labor activities. Around 22.14% household depend on their own cultivable land for production, 5.99% in various forma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 5 publications
2
3
0
Order By: Relevance
“…Such poor literacy level limited their opportunity to obtain a job in private or government of ices. As a result, all of them were involved in different low income jobs, conforming to the observations reported worldwide including Bangladesh [18,20]. Illiteracy is one of the constrains of pig industry since studies have shown that educated pig raisers can make more pro it than the uneducated ones [21,22].…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Such poor literacy level limited their opportunity to obtain a job in private or government of ices. As a result, all of them were involved in different low income jobs, conforming to the observations reported worldwide including Bangladesh [18,20]. Illiteracy is one of the constrains of pig industry since studies have shown that educated pig raisers can make more pro it than the uneducated ones [21,22].…”
Section: Discussionsupporting
confidence: 76%
“…Two third of the pig raisers were landless. As a result, these landless pig raisers face vulnerability of livelihood and economic opportunities which force them to engage in different low income jobs, and lead very substandard life in terms of food, housing, education and health facilities and exactly similar situations have been reported from earlier studies [16,20,23], indicating there receding, traditional and stagnant livelihood .…”
Section: Discussionsupporting
confidence: 61%
“…Though their lifestyles and characteristics are somewhat different from other people, the socioeconomic conditions of this community, along with other exploited classes properly, are because they have been living in all the parts of the subcontinents (Uddin, 2015). They involved too low social conditions that changed their traditional occupation and engaged in new occupations (Toppo, Rahman, Ali, & Javed, 2016). The majority of children in the community are deprived of education as well as there is no historical evidence that they were rewarded financially or socially (Pal, Mazumder, Akter, Khatun, & Alam, 2017).…”
Section: Introductionmentioning
confidence: 97%
“…The customs and culture of T communities are different from NT populations though they are living in the same region. Also, the food habits and behavior attitudes of tribes are different from the NT population [20]. The nutritional status of adults is related to socio-economic, demographic, cultural and behavioral factors.…”
Section: Introductionmentioning
confidence: 99%